Linking central auditory deficits to cognitive decline in mice with amyloid deposition: Development of new models and analysis methods/amyloid/Abeta. (7th December 2020) - Wang, Aaron; Lawlor, Jennifer; Fogelson, Kelly; Kuchibhotla, Kishore
Abstract: Background: Alzheimer's disease (AD) is a form of dementia that is characterized by the progressive loss of cognitive capacity, including the loss of executive functions and memory. There is growing evidence suggesting that hearing loss and dementia are tightly linked, with recent studies showing that hearing loss is independently associated with accelerated cognitive decline. However, the neural mechanisms linking hearing loss to AD‐related pathologies and subsequent cognitive decline remain unknown. Method: We will test the hypothesis that amyloid pathology impacts feedforward sensory processing in primary auditory cortex (A1). We performed in vivo two‐photon calcium imaging in awake, head‐fixed APPswe/PS1dE9 (APP/PS1) mice to investigate how AD pathology impacts central auditory processing. APP/PS1 mice express chimeric mouse/human amyloid precursor protein (APP) and mutant presinilin‐1 (PS1). These transgenes target neurons of the central nervous system and lead to the rapid accumulation of soluble amyloid beta and subsequent plaque deposition in cortical and hippocampal areas. Our study uses the fine‐scale tonotopic arrangement of excitatory neurons in A1 as an assay for feedforward sensory integration. With two‐photon calcium imaging, we have the spatial and temporal resolution to monitor the activity of hundreds of neurons simultaneously with single‐cell resolution. Result: Preliminary data collected from 11 mice (7 APP+, 4 WT) suggests clear differences in the processing of feedforward sensory information, namely differences in the tonotopic arrangement of neurons in A1 between WT and APP/PS1 mice. Conclusion: Future work will investigate how AD pathology affects sensorimotor learning. Learning rates will be monitored in APP/PS1 mice trained on a go/no‐go stimulus recognition task. To probe the neural computations that are critical for the selection of auditory cues during behavior, excitatory networks in A1 will be monitored using two‐photon calcium imaging while animals perform the task. This study hopes to elucidate neural mechanisms of how amyloid beta pathology impacts central auditory processing, and thus, mechanistically link hearing loss, AD‐related pathologies and cognitive impairments.